PERSESPSI SISWA TERHADAP KOMPETENSI GURU IPA DALAM MENGGUNAKAN PEMBELAJARAN YANG BERDIFERENSIASI DI SMP NEGERI 1 MEGO - Hadi Jaya Putra, Sukarman; Anjelina Nggona, Maria; Mansur S (Jurnal Biogenerasi, 2024)
This study aims to evaluate students' perceptions of science teachers' competencies in implementing differentiated instruction at SMP Negeri 1 Mego. Teachers' competencies in meeting the demands of the Merdeka Curriculum, which emphasizes adaptive and responsive learning tailored to the diverse needs of students, are deemed crucial. The research employed a descriptive quantitative approach, with data collected through questionnaires. The results show that the science teachers' competencies fall into the low category, with an average score of 32.43%. The breakdown includes pedagogical competence at 34.21%, social competence at 37.10%, and differentiated instruction ability at 35.04%. The low pedagogical competence indicates a lack of ability to adapt teaching methods to students' needs. Similarly, the low social competence reflects suboptimal interpersonal relationships between teachers and students. The inadequate implementation of differentiated instruction suggests a deficiency in teaching strategies that are responsive to the varying abilities, interests, and learning styles of students. The study concludes that efforts to enhance teachers' competencies are necessary through intensive training, academic supervision, and the development of professional learning communities. With sustained support from schools and the government, teachers are expected to improve their competencies, making learning more effective and aligned with students' needs.